Membangun Gerakan Literasi Sekolah dengan Mereview Buku Menggunakan Teknik Ishikawa Fishbone (Studi Kasus pada Kelas V SDN Cinangka 03 Kabupaten Bandung) - Daniar Asyari; Agil Nanggala (Departement of Mathematics Education, 2023)
This study aims to analyze the positive benefits of reviewing books using the Ishikawa Fishbone technique in increasing student literacy at SDN Cinangka 03. The research method used is qualitative research with case studies. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques used to reduce data, present data and conclude data. The results of this study show that students are trained to develop a sense of mutual cooperation, besides that the Ishikawa Fishbone technique can make it easier for students to understand the points contained in the enrichment book, so this technique is highly recommended to be applied especially in learning their reading skills. The Ishikawa Fishbone model is an attempt to develop high-level thinking skills and critical thinking for Cinangka 03 Elementary School students. The conclusion of this study is that this model trains students to understand and analyze the contents of a book properly and correctly and can improve students' reading skills.